2009
DOI: 10.1007/s00262-009-0782-8
|View full text |Cite
|
Sign up to set email alerts
|

Immunologic and prognostic factors associated with overall survival employing a poxviral-based PSA vaccine in metastatic castrate-resistant prostate cancer

Abstract: A concurrent multicenter, randomized Phase II trial employing a recombinant poxviral vaccine provided evidence of enhanced median overall survival (OS) (p=0.0061) in patients with metastatic castrate-resistant prostate cancer (mCRPC). The study reported here employed the identical vaccine in mCRPC to investigate the influence of GM-CSF with vaccine, and the influence of immunologic and prognostic factors on median OS. Thirty-two patients were vaccinated once with recombinant vaccinia containing the transgenes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
279
1
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 276 publications
(295 citation statements)
references
References 25 publications
11
279
1
3
Order By: Relevance
“…8,9 In addition, other approaches including vaccines that decrease the frequency and function of Tregs have also shown limited clinical benefits for cancer patients. 10,11 However, the role of Tregs in human CRC patients is still controversial. [12][13][14][15][16] Given the inconsistent results concerning the prognostic value of Tregs in patients with CRC, it is not surprising that there is to date no clinical trial reporting effective immunotherapies targeting Tregs in CRC.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 In addition, other approaches including vaccines that decrease the frequency and function of Tregs have also shown limited clinical benefits for cancer patients. 10,11 However, the role of Tregs in human CRC patients is still controversial. [12][13][14][15][16] Given the inconsistent results concerning the prognostic value of Tregs in patients with CRC, it is not surprising that there is to date no clinical trial reporting effective immunotherapies targeting Tregs in CRC.…”
Section: Introductionmentioning
confidence: 99%
“…This is based on the hypothesis that immune boosting of peptide-specific CTLs will be more effective than priming of naive T cells in inducing immunologic response. Other studies of PPV therapy, given concurrently with hormone therapy and low-dose EMP, have shown promising clinical and immunologic activity [1,2]. In the current study by Uemura et al [3], PPV monotherapy was assessed in 23 HLA-A24+ or A2+ patients with CRPC in a single arm study, to evaluate PPV monotherapy without concurrent EMP or hormone therapy.…”
Section: News and Views News And Views News And Viewsmentioning
confidence: 99%
“…Evaluation of a randomized Phase II trial of a poxviral-based PSA-targeted immunotherapy in patients with minimally symptomatic metastatic CRPC Recombinant vaccinia vector containing the entire PSA transgene with agonist epitope (rV-PSA) is a novel immunotherapy platform that has demonstrated activity in a Phase I trial in men with CRPC [1]. Preclinical studies have shown activity with first the addition of three costimulatory molecules along with the PSA transgene (rV-PSA-TRICOM) and second use of GM-CSF as an adjuvant to recruit dendritic cells [2,3]. A randomized Phase II trial previously demonstrated that a vaccinia vector prime (rV) followed by multiple fowlpox (rF) boosts had improved progression-free survival (PFS) compared with all-vaccinia or allfowlpox vaccination [4].…”
Section: News and Views News And Views News And Viewsmentioning
confidence: 99%
See 2 more Smart Citations